"A Trail of Drift and Debris": Traces of Whitman in the Correspondence Art of Ray Johnson. (February 2015) - ANDERSON, FIONA
<x content-type="archive" xml:space="preserve">Abstract</x> In 1987, the artist Ray Johnson, "leader" of the so-called New York Correspondence School, filled his mouth with Reese's Peanut Butter Cups and read some of Walt Whitman's musings on the nature of correspondence in a performance that Johnson dubbed Smile. An example of what Johnson termed his "nothings, " Smile took place in an empty ATM vestibule on Long Island, the nostalgic "Paumanok" of Whitman's poetry. Johnson's performance both elevated and mocked Whitman's equally personal approach to the art and practice of correspondence. By invoking Whitman and his thoughts on correspondence, Johnson was keen to respond to descriptions of him as "Dada Daddy" to a younger generation of correspondence artists. Johnson's performance looked not so much to elevate his own ephemeral correspondence art, but to foster a reappraisal of Whitman that considered the ephemerality of his poetic method and opened up a queer line of communication and anti-teleological influence that would disrupt Johnson's own artistic reception. This article examines Smile as an (auto)biographical performance that simultaneously clarifies and clouds the creative methodologies of Johnson and Whitman, declaring Whitman's influence on the irreverent Johnson while rejecting the restrictions of a chronological chain of influence, much as Johnson's earlier mail art had done.